Social Integration: Conceptual Foundations and Open Questions. An Introduction to this Special Issue - Daniela Grunow; Patrick Sachweh; Uwe Schimank; Richard Traunmüller (KZfSS Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2023)
Is the social integration of contemporary Western societies at risk? We will not provide an answer to this question, which is high on the political agenda. Instead, in our introduction to this special issue, we first offer conceptual clarifications. What is a~theoretically sound and empirically useful understanding of the social integration of modern societies? Second, we ask three basic questions for which adequate answers have not yet been found: (1)~How is social integration generated? That is, what are its central mechanisms? (2)~Is social integration a~functionally necessary precondition of societies, as concerns about its erosion suggest? Or is it a~goal in itself, that is, a~normatively desirable state? (3)~What about the dark side of social integration, i.e., its unintended or tacitly accepted side effects for society, its individual members, or particular social groups? – – Ist der soziale Zusammenhalt in modernen westlichen Gesellschaften gefährdet? Wir werden keine Antwort auf diese Frage geben, die ganz oben auf der politischen Agenda steht. Stattdessen bieten wir in unserer Einleitung zu diesem Sonderheft zunächst konzeptionelle Klärungen an. Was ist ein theoretisch fundiertes und empirisch nützliches Verständnis der Sozialintegration moderner Gesellschaften? Zweitens stellen wir drei grundsätzliche Fragen, auf die bisher keine adäquaten Antworten gefunden wurden: (1)~Wie wird Sozialintegration erzeugt? D. h. welches sind ihre zentralen Mechanismen? (2)~Ist Sozialintegration eine funktional notwendige Voraussetzung für Gesellschaften, wie die Sorge um ihre Erosion andeutet? Oder ist sie ein Ziel an sich, d. h. ein normativ erstrebenswerter Zustand? (3)~Wie sieht es mit den Schattenseiten der Sozialintegration aus, d. h. mit ihren unbeabsichtigten oder stillschweigend akzeptierten Nebenwirkungen für die Gesellschaft, ihre einzelnen Mitglieder oder bestimmte soziale Gruppen?
Keywords: 300; Modern society; Conflict; Social cohesion; Social solidarity; Social inequality; Moderne Gesellschaft; Konflikt; Soziale Kohäsion; Soziale Solidarität; Soziale Ungleichheit